2019
DOI: 10.1002/pts.2485
|View full text |Cite
|
Sign up to set email alerts
|

Migration of bisphenol a into food simulants and meat rations during initial time of storage

Abstract: The aim of this work was to assume the amount of BPA that can migrate to food packed into the cans coated by epoxy‐phenolic lacquer. The assumption was made by determining the amount of BPA which migrates from the inner can coating to different food simulants: 3% acetic acid, 10% ethanol, their mixture (3% acetic acid +10% ethanol), and 50% ethanol. The examined tinplate cans were made by the special requirements of the Serbian Armed Forces. Further, the effect of the sterilization process and the very initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…This work suggests that the safest packaging material to store nuts for a long period of time is glass. Furthermore, the quantification results clearly indicate that BPA leaching increases linearly with storage time and that temperature is the key factor that determines the migration percentage, as it also has been recently reported [32]. Comparing cans and polycarbonate packages, BPA was detected in higher concentrations when stored in polycarbonate.…”
Section: Analysis Of Nuts Stored Under Different Conditionssupporting
confidence: 70%
“…This work suggests that the safest packaging material to store nuts for a long period of time is glass. Furthermore, the quantification results clearly indicate that BPA leaching increases linearly with storage time and that temperature is the key factor that determines the migration percentage, as it also has been recently reported [32]. Comparing cans and polycarbonate packages, BPA was detected in higher concentrations when stored in polycarbonate.…”
Section: Analysis Of Nuts Stored Under Different Conditionssupporting
confidence: 70%
“…Similarly, Stojanovic et al examined the content of BPA in canned meat balls immediately after sterilization process and storing the samples at two different temperatures (20 and 40 °C) from 15 to 105 days. The authors observed the amount of BPA increased from 5 to 23.5 µg/kg (at 20 °C) and from 20 to 30 µg/kg (at 40 °C) after 15 days, further storage, however, lead to a very slow increase of BPA level [ 75 ]. Indeed, Munguia-Lopez et al reported no significant differences in BPA concentration in samples stored for either 40 or 70 days, although BPA levels increased following storage for 160 days at 25 °C [ 74 ].…”
Section: Bpa Contamination In Canned Meat Productsmentioning
confidence: 99%
“…The tinplate base is steel that provides good mechanical properties, while the tin coating gives a glossy appearance and protects the steel from corrosion (Arcelor Mittal 2013;Nikčević-Grassino et al 2010). For the Serbian Armed Forces' needs, the application of tin is a minimum of 5.6 g/m 2 on external and internal can surfaces (E-5.6/5.6), which is twice as high as for civilian use in Serbia (Stojanović et al 2019(Stojanović et al , 2020. Thanks to numerous advantages over other packaging types, tinplate packaging is most often used for the canned meat products.…”
Section: Introductionmentioning
confidence: 99%
“…For the needs of the Serbian Armed Forces, the application of varnish on the inner surfaces of the can is 6 g/m 2 , while on external surfaces is 5 g/m 2 (Stojanović et al 2019(Stojanović et al , 2020. Contamination of food with toxic elements is a global problem, and there are justi ably growing concerns about its safety.…”
Section: Introductionmentioning
confidence: 99%